Strategic Interventions for Character Development in the Era of Society 5.0: A Systematic Literature Review of Indonesian Higher Education - Siregar, Tiur Malasari; Sinaga, Fajar Apollo; Hutagalung, Trisnawati; Firdaus, Muliawan; Ramadhani, Irham; Tanjung, Yul Ifda; Sihombing, Rizky Agassy (Jurnal Pendidikan Progresif, 2025)
Strategic Interventions for Character Development in the Era of Society 5.0: A Systematic Literature Review of Indonesian Higher Education. Globalization has introduced foreign cultures that threaten students' moral integrity, making character education essential to shaping and preserving their identity. Objectives: This study analyzes strategic efforts in the campus environment as drivers of student character formation in the era of globalization. Methods: This study used a systematic literature review with a descriptive-qualitative approach to synthesize and analyze existing research on student character development. Data were collected from Google Scholar, Scopus, and ERIC databases, focusing on journal articles published over the last 10 years (2015-2025). The literature search used several databases with relevant keywords, applying inclusion and exclusion criteria based on study type, language, and publication period. From an initial search using the keyword "Student Character," based on title and abstract relevance, 27 articles focusing on practical character-building efforts were ultimately selected for thematic analysis. Findings: A critical evaluation reveals common methodological weaknesses in Indonesian character education studies: predominantly qualitative designs lacking quantitative validation, small sample sizes limiting generalizability, the absence of longitudinal studies for long-term assessment, and insufficient control groups to establish causality. Publication bias is evident, with studies predominantly reporting positive outcomes while minimizing limitations. The quality of evidence remains moderate, with few studies employing rigorous measurement instruments or validated character assessment tools. The quality of evidence remains moderate, with few studies employing rigorous measurement instruments or validated character assessment tools. Despite these limitations, this review highlights the effectiveness of integrating character-building through courses and extracurricular activities. Conclusions: Holistic models incorporating local wisdom, along with organizational activities such as scouting, student associations, and anti-corruption education, effectively foster essential traits involving tolerance, responsibility, critical thinking, independence, creativity, and honesty that support student identity in globalization contexts. However, future research requires more rigorous designs, standardized tools, and transparent reporting to strengthen the evidence for character education in Indonesian higher education. Keywords: analysis, student character, globalization.